Pengaruh Realisasi Transfer Dana Desa terhadap Peningkatan Pertumbuhan Ekonomi 62 Kabupaten di Indonesia - Muhammad Rizki; Osni Erza (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
The disparities in characteristics across regions in Indonesia can lead to unequal development. The central government directs development activities in the regions with a primary focus on villages and underdeveloped areas. The Village Fund, sourced from the state budget (APBN), is allocated to villages and can be used to finance various development activities, which are expected to be a solution to the development disparities in villages and underdeveloped areas. The objective of this research is to examine the impact of the realization of Village Fund Transfers on economic growth in 62 underdeveloped districts.